Reperfusion therapy for acute ischemic stroke: where are we in 2023? - Martins, Sheila Cristina Ouriques; Pontes-Neto, Octávio Marques; Pille, Arthur; Secchi, Thaís Leite; Miranda Alves, Maramélia Araújo de; Rebello, Letícia Costa; Oliveira-Filho, Jamary; Lange, Marcos Christiano; de Freitas, Gabriel R.; de Andrade, João Brainer Clares; Rocha, Letícia Januzi de Almeida; Bezerra, Daniel da Cruz; Souza, Ana Claudia de; Carbonera, Leonardo Augusto; Nogueira, Raul Gomes; Silva, Gisele Sampaio (Arquivos de Neuro-Psiquiatria, 2023)
Over the last three decades, stroke care has undergone significant transformations mainly driven by the introduction of reperfusion therapy and the organization of systems of care. Patients receiving treatment through a well-structured stroke service have a much higher chance of favorable outcomes, thereby decreasing both disability and mortality. In this article, we reviewed the scientific evidence for stroke reperfusion therapy, including thrombolysis and thrombectomy, and its implementation in the public health system in Brazil.
Keywords: Stroke; Ischemic Stroke; Reperfusion; Thrombolytic Therapy; Thrombectomy